Optimum welding parameter for GMA welding using soft computing techniques - Pedapati, S.R. (American Institute of Physics Inc., 2017)
In this paper, a study on the welding parameters for pipeline is done by application of Metal Inert Gas (MIG) welding by taking into account welding speed and wire feed rate as the parameters. These parameters are important to determine the tensile strength and weld bead penetration of the welded specimen. Large data sets are necessary to train the Neural Network using Matlab ANN tool and hence enable to predict the desired output. The predicted output is validated by comparing with experimental data. © 2017 Author(s).